Epidemiological impact and cost-effectiveness of introducing vaccination against serogroup B meningococcal disease in France. Issue 19 (27th April 2016) - Lecocq, Héloïse; Parent du Châtelet, Isabelle; Taha, Muhamed-Kheir; Lévy-Bruhl, Daniel; Dervaux, Benoit
Abstract: Introduction: Despite its low incidence in France, invasive serogroup B meningococcal disease remains a public health concern. A new vaccine against the disease, Bexsero ®, has been licensed in the EU. We studied the epidemiological impact and cost-effectiveness of routine vaccination using Bexsero ® in order to inform the decision-making process regarding its potential inclusion in the vaccination schedule. Methods: A multi-generational Markov model was used. Time horizon was set to 100 years. Five vaccination strategies were evaluated: infants at 3, 5, 6 and 13 months, toddlers at 13, 15 and 27 months and adolescents at 15 years provided 2 doses one month apart. A booster dose at 15 years old and a catch-up for 15 years old subjects during the first 15 years of the programme were added to the infant and toddler strategies. Costs per QALY gained were computed from a restricted societal perspective including direct costs only. Herd immunity was simulated in an alternative base-case scenario and sensitivity analyses. Results: In the base-case analysis without herd immunity and with all cohorts vaccinated, at €40 per vaccine dose, routine infant vaccination would provide the lowest cost per QALY gained (€380, 973) despite only preventing 18% of cases. Under the assumption of herd immunity, the adolescent vaccination would provide the lowest cost per QALY gained (€135, 902) preventing 24% of cases. Infant vaccination with a late booster and catch-up would prevent 51% of cases with a cost of €188, 511 per QALY gained. Conclusions: Given current meningococcal epidemiology in France and the available data on the protection provided by Bexsero ®, our modelling work showed that routine vaccination against serogroup B meningococcal disease is not cost-effective.